ANALISIS TINGKAT KESEHATAN BANK MENGGUNAKAN METODE CAMEL PADA LAPORAN KEUANGAN PT. BANK SYARIAH INDONESIA TAHUN 2021-2024 - Umairoh, Nisa Ul Anda; Khayati, Ismatul (LPPM Universitas Banten jaya, 2026)
Thisl study aims lto determine lthe health llevel of lPT. Bank lSyariah Indonesia (lBSI) Tbk inl 2021-2024. The assessmentl indicators usedl in lthis study lare Capital, lAsset Quality, lManagement, Earning, andl Liquidity lor abbreviated las CAMEL. Thel Camel methodl is one of the factors lthat greatly ldetermines the healthl of la bank. Thisl study wasl conducted withl a lquantitative descriptive lapproach, namely usingl secondary ldata obtained lfrom library sources such as academic journals, government publications and annual lfinancial reports published lon the lcompany's officiall website, lby analyzing lthe CAR, lNPF, PDN, lROA, ROE, lBOPO, NI, land FDR lratios. The resultsl of thel study lshowed that lthe CAR lratio for the 2021-2024 periodl was given the predicatel